About a Role and the Place of Plenipotentiary Representatives of the President of the Russian Federation in the Power Mechanism of Ensuring Military Safety of the Country - A. A. Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article, on the basis of the short analysis of history of creation and reforming of institute of Plenipotentiary Representatives of the President of the Russian Federation in regions and the main objectives assigned to them, the conclusion about need of cardinal reforming of this institute for his adaptation both to constitutional law of the Russian Federation, and to time calls is drawn.